2022
DOI: 10.1002/adem.202200171
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Spray Coatings for Electromagnetic Wave Absorption and Interference Shielding: A Review and Future Challenges

Abstract: This review aims to consolidate scattered literature on thermally sprayed coatings with nonionizing electromagnetic (EM) wave absorption and shielding over specific wavelengths potentially useful in diverse applications (e.g., microwave to millimeter wave, solar selective, photocatalytic, interference shielding, thermal barrier‐heat/emissivity). Materials EM properties such as electric permittivity, magnetic permeability, electrical conductivity, and dielectric loss are critical due to which a material can res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 203 publications
(379 reference statements)
0
10
0
Order By: Relevance
“…25,26 Significant reflection loss will attenuate the incident microwaves, and the absorption strength may be extended. 27,28…”
Section: Selecting the Pcf Composite With The Optimum Microwave Absor...mentioning
confidence: 99%
“…25,26 Significant reflection loss will attenuate the incident microwaves, and the absorption strength may be extended. 27,28…”
Section: Selecting the Pcf Composite With The Optimum Microwave Absor...mentioning
confidence: 99%
“…For a specific coating product, several factors, such as their concentration/ viscosity, how the coating is applied, the salinity of seawater, exposure to sunlight, stress corrosion cracking processes, etc., determine their released quantity (Kirchgeorg et al, 2018). Thus, developing new forms of protection against corrosion based on eco-friendlier materials with intrinsic durability, good substrate adhesion and adequate mechanical properties is key to withstand external stresses, mechanical solicitation, or weathering while minimizing the release of toxic substances during their application and operation times (Faisal et al, 2022;Teijido et al, 2022).…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…Electromagnetic metamaterials are special periodic structures which are designed and fabricated artificially; their periodic unit cell is much smaller than the wavelength of EM waves. [10][11][12] Their electromagnetic properties primarily depend on the unit structure of the metamaterials and not entirely on the intrinsic properties of the material itself. Some recent studies have reported that the EAB can be effectively widened using electromagnetic metamaterials.…”
Section: Introductionmentioning
confidence: 99%